Methodological note: Qualitative research methods to explore women’s leadership - Morgan, Miranda; Misra, Deepannita; Ravani, Khanjan; Kachhap, Apurwa; Madappa, P.S.; Elias, Marlene; Meinzen-Dick, Ruth S.; Priyadarshini, Pratiti (2023)
This Methodological Note seeks to support reflection on and provide examples of qualitative research methodologies to understand and assess women’s leadership, including leadership that supports collective action in the Commons.